(untitled) (Fiep Bulletin - online, 2012)
Exploratory study in a qualitative approach from the perspective of the theoretical support social representations with the objective of know the social representations about elderly falls second. Participated in the research one hundred and fifty elders belonging to the Family Health Unit - Living Well, the city of João Pessoa, Paraiba, Brasil. For data collection was used a semi structured subsidized in the theoretical framework of social representations. The data collected were organized into a database, and processed with the help of software Alceste: 2010 from a lexical analysis of textual material which showed five interrelated thematic categories or classes: experiences and strategies for prevention, risk factors, falls as synonymous with aging, aging and impact of the fall and images of aging and decline. There was a denial of the risk of falls among the elderly because they consider it as a common event of aging for this reason denies the risk of falling. The design of the elderly is the same as a normal event in the course of life and can only be treated as an important event to cause some damage, otherwise it is taken as a tropicão or fall.